Ketimpangan Kekuasaan dan Bias Hukum dalam Sengketa Lahan Rempang: Analisis Teori Konflik terhadap Relasi Pemerintah, Investor, dan Masyarakat Adat - Junita, Putri; Hilal, Cut Anastasya Nurul; Kholila, Marsya Ainun; Anasthalia, Deva; Kamal, Ubaidillah (Peneliti.net, 2025)
The land dispute on Rempang Island reflects the power imbalance between the government, investors, and indigenous communities. The development of Rempang Eco-City, which is fully supported by the state, has caused agrarian conflict because it ignores the customary rights of communities that have lived there for more than two centuries. From a conflict theory perspective, the law is not neutral, but rather a tool of domination used by powerful groups to defend their economic interests. The granting of a Land Use Right (HGU) to PT Makmur Elok Graha without consulting the indigenous community highlights the legal system's bias toward investors. This study uses a literature review method to analyze biases in legal implementation and power imbalances in the Rempang conflict. The analysis shows that the law favors the interests of the state and capital, while indigenous communities are marginalized without adequate legal protection. Therefore, agrarian policy reform and a more participatory approach are needed to achieve social justice.